Talaandig mothers’ engagement for sustainable peace - Villaluz, Geraldine Delos Cientos (IAIN Madura, 2024)
The need for more contextualized literature for peace education courses in Central Visayas has become demanding for teachers seeking comprehensible peace concepts from indigenous perspectives. Concepts on peace introduced in universities’ undergraduate and graduate programs are published documents from Western experiences underlined by resolutions from the United Nations conferences on peace. This study sought to draw out peace concepts from the perspectives of Indigenous women who are conflict-settling mothers of the Talaandig tribe in northern Mindanao, Philippines, to contribute to the literature gap in peace education courses. Ethnographic-grounded theory approaches in the qualitative methods applied Charmaz’s (2006) coding and memo-writing steps. Three objectives were laid out to draw out definitions of peace from Indigenous women’s perspectives, illustrate images of peace through a soil painting workshop, and contribute an educational framework for a culture of sustainable peace from Indigenous mothers’ peacekeeping strategies, designed into three research phases. Twenty-one mothers who are active in peacekeeping activities have been chosen by the mother coordinator as participants. This study has resulted in a pool of Indigenous concepts of peace drawn out from narratives of mothers’ engagements in conflict settling and peacekeeping, soil-painted images of peace illustrating values relevant to the needs of today’s world, and a working framework for peace education from Indigenous women’s perspectives. This joint work of mothers and academic communities opens possibilities for contextualized peace concepts and values responsive to today’s world.